2023
DOI: 10.3390/v15020326
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of BNT162b2, ChAdOx1-Sand mRNA-1273 Vaccines and Two Boosters: A Prospective Longitudinal Real-World Study

Abstract: To date, the effectiveness of COVID-19 vaccines and booster doses has yet to be evaluated in longitudinal head-to-head studies. This single-center longitudinal study assessed the effectiveness of ChAdOx1 nCoV-19, BNT162b2, and mRNA-1273 vaccines and assessed two BNT162b2 boosters in 1550 participants, of whom 26% had comorbidities. In addition, the SARS-CoV-2 antibody dynamics was monitored. A group of 1500 unvaccinated subjects was included as the controls. The study’s endpoint was the development of virologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Tfh cells are essential for B‐cell maturation, neutralizing antibody production, and long‐term humoral immunity establishment (Meckiff et al, 2020; Rydyznski Moderbacher et al, 2020). CD8 + T‐cell immunity significantly contributes to the protective efficacy of SARS‐CoV‐2 vaccines (Kamal et al, 2023; McCallum et al, 2021a; Shen et al, 2021a; G.‐L. Wang et al, 2021).…”
Section: Virus Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tfh cells are essential for B‐cell maturation, neutralizing antibody production, and long‐term humoral immunity establishment (Meckiff et al, 2020; Rydyznski Moderbacher et al, 2020). CD8 + T‐cell immunity significantly contributes to the protective efficacy of SARS‐CoV‐2 vaccines (Kamal et al, 2023; McCallum et al, 2021a; Shen et al, 2021a; G.‐L. Wang et al, 2021).…”
Section: Virus Variantsmentioning
confidence: 99%
“…Tfh cells are essential for B-cell maturation, neutralizing antibody production, and long-term humoral immunity establishment(Meckiff et al, 2020;Rydyznski Moderbacher et al, 2020). CD8+ Tcell immunity significantly contributes to the protective efficacy of SARS-CoV-2 vaccines(Kamal et al, 2023;McCallum et al, 2021a;Shen et al, 2021a;G.-L. Wang et al, 2021) Yorsaeng et al (2022a). indicated that CD8+ T cells are important effector cells that are expanded during an early protection window after prime vaccination.…”
mentioning
confidence: 99%